The Dilemma of Criminal Liability for the Operation of Motorized Pedicabs in Yogyakarta Due to the Absence of Explicit Regulations Accommodating Them as a Mode of Public Transportation - Ruwito, Amin; Joko Setiono; Supardi Hamid (Jurnal Greenation Sosial dan Politik, 2025)
The phenomenon of motorized pedicab (bentor) operations in Yogyakarta reflects a shift in public demand toward faster and more efficient modes of transportation. However, the presence of a bentor faces a legal dilemma due to the absence of explicit regulations accommodating it within both national and regional legal systems. Law No. 22 of 2009 on Road Traffic and Transportation and Regional Regulation (Perda) of Yogyakarta Special Region (DIY) No. 5 of 2016 only regulate official and traditional transportation modes, without specifically addressing modified forms such as bentor. This legal ambiguity raises questions regarding the legal status of bentor and the extent to which its drivers can be held criminally liable. This study employs a normative juridical method with statutory and conceptual approaches, aiming to analyze the existing legal vacuum and its impact on law enforcement and social justice. The study finds that although the operation of bentor may be considered administratively unauthorized, the application of criminal law to its drivers encounters obstacles related to the principle of legality, as no criminal norm explicitly prohibits such activity. Moreover, enforcement actions carried out without an adequate legal basis have the potential to create injustice and discrimination. This research recommends revising regional regulations to be more accommodating of alternative modes of transportation, adopting a conditional legalization approach, and encouraging intergovernmental collaboration. Responsive regulation is key to ensuring legal order while upholding social and humanitarian values.